Investigating the Impact of Artificial Intelligence on Multiple Intelligences in English Language Classrooms - Sakakini, Dr. Adel; Hussein, Dr. Rania (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
One of the primary goals of 21st-century pedagogy is to promote learner-centered and personalized instruction in today’s rapidly evolving educational setting. Traditional classroom methods frequently place too much emphasis on verbal intelligence at the detriment of other learning strengths, despite Gardner's Multiple Intelligences (MI) theory emphasizing the necessity to address multiple learning strengths. In this context, educators are encouraged to design specific strategies that match acknowledge the cognitive diversity of students. As artificial intelligence (AI) becomes more prevalent in education, there are more chances to create learning environments that appeal to several intelligences at once. This paper presents a narrative literature review exploring the intersection of AI and MI in English language classrooms. It examines how AI applications align with Multiple intelligences theory in language learning contexts. Results show that AI technologies including chatbots, grammar checkers, adaptive learning systems, virtual reality, and AI-powered collaborative tools may assist a variety of intelligences by boosting motivation, encouraging multimodal engagement, and personalizing learning paths. However, there are some challenges include teacher readiness, cultural biases in AI, and ethical concerns. Overall, the findings suggest that an integration between AI practices and MI instruction can enhance students’ engagement and peronalized learning in English language classrooms.